Ionic liquid-modified carbon-based fillers and their polymer composites - A Raman spectroscopy analysis - Shamsuri, Ahmad Adlie; Mohamed Yusoff, Mohd Zuhri; Abdan, Khalina; Md. Jamil, Siti Nurul Ain (Walter de Gruyter GmbH, 2024)
In the field of advanced materials, carbon-based fillers are crucial for crafting high-performance polymer composites. Continual innovations in modifying these fillers are expanding the capabilities of polymer composite materials, heralding new advancements in diverse technological areas. Ionic liquids provide innovative methods for modifying carbon-based fillers to improve the performance of polymer composites. In this concise review, numerous carbon-based fillers used for modification, ionic liquids utilized in the modification, and polymer matrices employed in polymer composites are classified. In addition, the impact of ionic liquids on the interactional and structural properties of carbon-based fillers and their polymer composites, as analyzed via Raman spectroscopy, is concisely explained. This review provides a succinct analysis that deepens the understanding of the Raman spectroscopic results pertaining to various carbon-based fillers and polymer composites. In brief, Raman analyses indicate that carbon-based fillers modified with ionic liquids and their composites exhibit upshifted peak positions and higher intensity ratios compared to their unmodified fillers. The upshifts in peak positions are linked to interactions between the fillers and ionic liquids or between the modified fillers and polymer matrices. Higher intensity ratios in these modified fillers and polymer composites suggest increased structural defects in the fillers.